Simple, robust and near optimal designs for the estimation of log-logistic dose response functions - Tim Holland-Letz; Annette Kopp-Schneider (Archives of Toxicology, 2026)
Experimental designs in dose response experiments often use simple setups where the dose levels are increased by a fixed factor on the log scale. More efficient or even formally optimal experimental designs exist for this context, but these are often unpopular among applied scientists as they usually depend on the true value of some of the parameters and also frequently propose using only a small number of distinct dose levels. On the other hand, more generally optimal designs such as quasi-bayesian designs are often quite complicated, and still require specifying an a-priori distribution of parameters. In this paper we propose a single graphical representation which shows the performance of any given experimental design under a wide range of possible parameters. Using this representation, we propose four different possible designs which are both simple and still provide reasonable efficiency under many parameter constellations, without needing anything but the most coarse prior knowledge about these parameters. Specifically, our recommended design proposes 10 different dose levels in total, 8 main doses spaced equally around the most likely ED 50 value, exactly one natural log step apart, and one more set of observations each under control, and under the maximum technically feasible dose. The available observations should be distributed among these dose levels so that each of the main dose levels is assigned roughly $$4.7%$$ of the observations, while control and maxdose are assigned roughly $$19.6%$$ of the observations, rounding when necessary.

Transgenic HPV11-E2 protein modulates URR activity in vivo - Shubei Wang; Vera Gramm; Elke Laport; Tim Holland-Letz; Angel Alonso; Johannes Schenkel (Transgenic Research, 2023)
In vitro experiments have shown that the E2 protein of human papillomaviruses (HPV) binds to the upstream regulatory region (URR) of the viral genome and modulates transcription. Additionally, it seems to be a necessary component for viral DNA replication together with E1. We have developed a transgenic mouse model containing the URR region of the low-risk virus HPV11 that regulates the expression of the lacZ reporter gene. Most interestingly, in these mice, the transgene was exclusively expressed in the bulge region of the hair follicle but not in any other tissues. Further experimental data indicate that in double transgenic mice that also express the HPV11-E2 protein under the control of the Ubiquitin C-promoter, the transcription of the reporter gene is modulated. When E2 is present, the expression of the reporter gene also occurs exclusively in the bulge region of the hair follicles as it does in the single transgenic mice, but the expression of the lacZ driven by the URR is increased and the statistical spread is greater. Even if the expression of the reporter gene occurs in the hair follicles of the dorsal skin of an animal uniform, E2 obviously has the capacity for both to induce and to repress the URR activity in vivo.

Modeling dose–response functions for combination treatments with log-logistic or Weibull functions - Tim Holland-Letz; Alexander Leibner; Annette Kopp-Schneider (Archives of Toxicology, 2020)

Optimal experimental designs for dose–response studies with continuous endpoints - Tim Holland-Letz; Annette Kopp-Schneider (Archives of Toxicology, 2015)